Anti-bacterial and Anti-biofilm Effect of Curcumin-Ag Nanoparticles against Pseudomonas aeruginosa Isolated from Iraqi Burn Patients Infections - Rasha Mohammed Sajet Al-Oqaili; Seyyed Meysam Abtahi Froushani; Likaa Hamied Mahdi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The increasing emergence of multidrug-resistant bacteria, which are the cause of wound infections, constitutes a major health problem, and because of their ability to produce biofilms. The main objective of the present study is to evaluate the antibacterial and antibiofilm activity of curcumin-Ag nanoparticles. According to Scanning Electron Microscopy (SEM) and X-Ray Diffraction analysis (XRD), the nanoparticles appeared in spherical shapes and sizes of 47.98 - 58.80 nm. From UV-Visible spectrum a high-intensity absorption peak around 450 nm called the spectral plasmonic region (SPR), is observed for curcumin-Ag. To examine the antibacterial activity, the agar-well diffusion method was performed. Minimum inhibitory concentrations (MIC) of curcumin-Ag nanoparticles and gentamicin were used to evaluate the antibacterial activity against resistant Pseudomonas aeruginosa. The results indicate that nano-curcumin possesses material anti-bacterial activity against all Ps. aeruginosa isolates disparity with control, and the anti-bacterial activity of nano-curcumin at 256 μg/ml was significantly higher than 128 μg/ml, according to earlier research, curcumin nanoparticles break down bacterial cell walls, and when this happens, the bacteria lyse and die. Antibiotic susceptibility testing was performed on Piperacillin (70%), Imipenem (53.33%), Colstine (40%), Gentamycin (0%), and Ceftaroline (CFT) (30%). Signiﬁcant antibacterial action of curcumin NPs was observed against the most biofilm-producing Ps. aeruginosa isolates.